Free breathing 1H MRI of the human lung with an improved radial turbo spin-echo - Völker, Michael; Biederer, Jürgen (Magnetic resonance materials in physics, biology and medicine, 2015)
Objective To optimize a radial turbo spin-echo sequence for motion-robust morphological lung magnetic resonance imaging (MRI) in free respiration.Materials and methods A versatile multi-shot radial turbo spin-echo (rTSE) sequence is presented, using a modified golden ratio-based reordering designed to prevent coherent streaking due to data inconsistencies from physiological motion and the decaying signal. The point spread function for a moving object was simulated using a model for joint respiratory and cardiac motion with a concomitant T2 signal decay and with rTSE acquisition using four different reordering techniques. The reordering strategies were compared in vivo using healthy volunteers and the sequence was tested for feasibility in two patients with lung cancer and pneumonia.ResultsSimulations and in vivo measurements showed very weak artifacts, aside from motion blur, using the proposed reordering. Due to the opportunity for longer scan times in free respiration, a high signal-to-noise ratio (SNR) was achieved, facilitating identification of the disease as compared to standard half-Fourier-acquisition single-shot turbo spin-echo (HASTE) scans. Additionally, post-processing allowed modifying the T2 contrast retrospectively, further improving the diagnostic fidelity.ConclusionThe proposed radial TSE sequence allowed for high-resolution imaging with limited obscuring artifacts. The radial k-space traversal allowed for versatile post-processing that may help to improve the diagnosis of subtle diseases.